Acting for singers : creating believable singing characters - Ostwald, David, 1943- (Oxford, 2005)
Explains how to analyse a script of libretto, shows how to develop a character building on material in the score, and gives the singing performer the tools to act believably. This book addresses the problems of concenration, trust, and projection, among others, and includes concrete examples from opera and musical theatre.